Black Genders and Sexualities - McGlotten, S.; Davis, D.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2012)
Cutting across the humanities and social sciences, and situated in sites across the black diaspora, the work in this book collectively challenges notions that we are living in a post-racial age and instead argue for the specificity of black cultural experiences as shaped by gender and sex.
Keywords: Sociology; Ethnicity; Social justice; Human rights; Gender Studies; Ethnicity Studies; Social Justice, Equality and Human Rights